Gambaran Pengetahuan dan Perilaku Personal Hygiene Siswa SDN 19 Temajuk Kecamatan Paloh Kabupaten Sambas Tahun 2022 - Murti, Dwi; Saepudin, Malik; Prayetno, Bambang (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
Personal Hygiene was an individual or group effort to maintain health through cleanliness. It had a significant role in the growth and development of a child because elementary school children aged 6 to 12 years have a body that was vulnerable to health problems. This study aimed to describe the knowledge and behavior of Personal Hygiene students of SDN 19 Temajuk, Paloh District, Sambas Regency. This research was a descriptive study with a research population of 51. The research sample was 47 respondents consisting of 4th grade and 5th grade students. Data was collected by filling out questionnaires and observations. The result of good knowledge research was 34 (72.34%) respondents, 9 (19.15%) respondents were sufficient, and 4 (8.51%) respondents were lacking. Sufficient behavior was 25 (53.19%) respondents, 15 (31.91%) good respondents and 7 (14.9%) less respondents. The conclusion of this study was that the knowledge of Personal Hygiene of grade 4 and 5 at the SDN 19 Temajuk has mostly good knowledge. Meanwhile, the Personal Hygiene behavior of students is still in the sufficient category. The author suggests that students can apply better Personal Hygiene behavior.